Asuhan Keperawatan Keluarga Dengan Anggota Keluarga Mengalami Gangguan Mobilitas Fisik Pasca Stroke Di Masa Pandemi Covid-19 Di Desa Sooko Kec. Sooko Kab. Mojokerto - Yudha Laga Hadi Kusuma; Shofiyatun Nada (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Family support is very important in optimizing the health of sick family members. The purpose of this case study is for families to be able to care for a family member experiencing impaired physical mobility after a stroke at home to minimize going to health facilities due to the COVID-19 pandemic. The design used in this research is a case study, using 2 families, then nursing care diagnoses, interventions, implementation and evaluation are made. The diagnosis of impaired physical mobility is related to the inability of the family to care for sick family members. Methods of data collection by interview, observation, and documentation using the format of family nursing care. The results obtained from the study are that families are unable to care for sick family members. Interventions and implementations carried out are planning ROM (Range of Motion) therapy according to needs, teaching clients and families about ROM. The evaluation found that the family of client 1 and client 2 said that they could care for family members who had impaired physical mobility after stroke with ROM